The role of Fiscal policy in Britain's Great Inflation - Jingwen Fan; Patrick Minford; Zhirong Ou (Cardiff University, Cardiff Business School, 2014)
We investigate whether the Fiscal Theory of the Price Level (FTPL) can explain UK inflation in the 1970s. We confront the identification problem involved by setting up the FTPL as a structural model for the episode and pitting it against an alternative Orthodox model; the models have a reduced form that is common in form but, because each model is over-identified, numerically distinct. We use indirect inference to test which model could be generating the VECM approximation to the reduced form that we estimate on the data for the episode. Neither model is rejected, though the Orthodox model outperforms the FTPL. But the best account of the period assumes that expectations were a probability-weighted combination of the two regimes. Fiscal policy has a substantial role in this weighted model. A similar model accounts for the 1980s though the role of fiscal policy gets smaller.
Keywords: E31; E37; E62; E65; 330; UK Inflation; Fiscal Theory of the Price Level; Identification; Testing; Indirect inference